Some girls : my life in a Harem - Lauren, Jillian (London : Plume, 2010)
At eighteen, Jillian Lauren was an NYU theater school dropout with a tip about an upcoming audition. The "casting director" told her that a rich businessman in Singapore would pay pretty American girls $20,000 if they stayed for two weeks to spice up his parties. Soon, Jillian was on a plane to Borneo, where she would spend the next eighteen months in the harem of Prince Jefri Bolkiah, youngest brother of the Sultan of Brunei, leaving behind her gritty East Village apartment for a palace with rugs laced with gold and trading her band of artist friends for a coterie of backstabbing beauties.